Pengaruh Literasi Keuangan dan Perilaku Keuangan terhadap Minat Investasi Mahasiswa Universitas Palangka Raya dengan Self control sebagai Variabel Mediasi - Yunita Sella; Cecilia Herminanda; Sovia Kristina Sosi (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the effect of financial literacy and financial behavior on investment intention among Universitas Palangka Raya students, with self-control as a mediating variable. Data were analyzed using Structural Equation Modeling based on Partial Least Square with SmartPLS. The measurement model met validity and reliability criteria, as shown by outer loading values above 0.70, AVE values above 0.50, and Cronbach's alpha and composite reliability values above 0.70. The structural model showed that financial literacy had a positive and significant effect on investment intention (O = 0.418; t = 4.816; p = 0.000). Financial behavior also had a positive and significant effect on investment intention (O = 0.336; t = 3.122; p = 0.002) and self-control (O = 0.463; t = 4.045; p = 0.000). Financial literacy did not significantly affect self-control, and self-control did not significantly affect investment intention. The indirect effects also showed that self-control did not mediate the effect of financial literacy or financial behavior on investment intention.